The influence of minimalist footwear on knee and ankle load during depth jumping - Sinclair, J.; Hobbs, S. J.; Selfe, J. (Research in Sports Medicine, 2015)
Plyometric training is used by athletes to promote strength and explosive power. However plyometric activities such as depth jumping are associated with a high incidence of injuries. This study examined the influence of minimalist and conventional footwear on the loads experienced by the patellofemoral joint and Achilles tendon. Patellofemoral and Achilles tendon forces were obtained from ten male participants using an eight-camera 3D motion capture system and force platform data as they completed depth jumps in both footwear conditions. Differences between footwear were calculated using paired t-tests. The results show that the minimalist footwear were associated with significantly lower patellofemoral contact force/pressure and also knee abduction moment. It is therefore recommended, based on these observations, that those who are susceptible to knee pain should consider minimalist footwear when performing plyometric training.